Long-read, multi-amplicon sequencing to explore genetic diversity associated with starch degrading phenotypes in amylolytic Lactobacillaceae - Olivier, Sandra A.; Bull, Michelle K.; Bowman, John P.; Ross, Tom; Chapman, Belinda (Frontiers in Microbiology, 2025)
Characterizing starch-degrading Lactobacillaceae and associated enzymes remains relevant as various industries seek to harness their activity to produce valuable by-products, develop novel food applications, and to aid the sustainable bioconversion of starch-rich resources. To support this, we developed a targeted methodological and analysis framework utilizing complimentary phenomic and genomic assays informative of the starch degrading potential of Lactobacillaceae. Adapted starch agar plate assays incorporating diversified starch sources and states facilitated the rating of extracellular amylolytic activity by starch-processing-line isolates [Lactobacillus amylovorus (n = 3), Lactobacillus amylolyticus (n = 2), and Limosilactobacillus reuteri (n = 2)] as weak to moderate based on the complete or partial hydrolysis of retrograded soluble (SS), or potato and wheat (WS), starches, respectively, and the partial hydrolysis of raw SS. In contrast, the known raw starch degrader, L. amylovorus NRRL B4540, was rated as strong, with complete hydrolysis of all retrograded starch sources and raw WS. To explore genetic diversity and the putative enzymes associated with phenotypic diversity amongst L. amylovorus and L. amylolyticus, a multi-amplicon sequencing approach using MinION™ was used to simultaneously sequence starch-degradation-associated genes identified from them. Gene and deduced amino acid sequence analysis suggested raw starch hydrolysis by L. amylovorus NRRL B4540 was largely attributed to amyA encoding a rare α-amylase with unique starch binding domain (targeting α-1,4 linkages), but which was predicted to also require the starch debranching activity (targeting α-1,6 linkages) associated with (putative) pul-encoded pullulanase (Pul) for complete hydrolysis. Without amyA, Pul was hypothesized necessary for observed starch degradation by L. amylovorus and L. amylolyticus test isolates; as a previously undescribed amylopullulanase with dual activity, or as a pullulanase requiring complimentary α-1,4 activity from an additional enzyme, potentially Gly2 (a putative maltogenic α-amylase). Whilst further work is required to characterize these enzymes, including those encoded by gene variants, the experimental approach described here provided the necessary evidence to warrant this. Further, this framework is likely adaptable for the direct analysis of Lactobacillaceae-rich microbiomes for amylolytic potential and for the targeted screening of various other functions across different taxa.